Tensions in Creating Possibilities for Youth Voice in School Choice: An Ethnographer’s Reflexive Story of Research - Cotnam-Kappel, Megan (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
The following article relates a reflexive ethnographic research project that focuses on youth voice in relation to the process of choosing a high school and a language of instruction in Ontario, Canada. The purpose of this methodological article is to relate a story of research and explore the tensions between theory and practice experienced by a young researcher during and after fieldwork. To do so, I explore the theoretical and epistemological underpinnings of the relevance and importance of youth-centred research and uncover some of the complexities of conducting participant observation, interviews, and co-analysis activities with youth participants. Résumé Cet article présente un projet de recherche ethnographique réflexif qui se concentre sur les perspectives des jeunes dans leur processus de sélection d’une école secondaire et d’une langue d’enseignement dans la province Canadienne de l’Ontario. Le but de cet article méthodologique est de raconter l’histoire d’un projet de recherche et d’explorer les tensions entre la théorie et la pratique vécue par une jeune chercheure pendant et après le travail de terrain. Pour ce faire, j’explore les fondements théoriques et épistémologiques de la pertinence et de l’importance de la recherche centrée sur les enfants, et de mettre en lumière les complexités de l’observation participante, des entretiens et des activités de co-analyse de données avec les jeunes participants.